INVESTASI CRYPTO: BAGAIMANA KEAMANAN, KEMUDAHAN, DAN PERSEPSI RISIKO MEMBENTUK PERSEPSI KEUNTUNGAN DAN KEPUTUSAN INVESTOR MUDA DI KOTA TANGERANG - Rosyid Rosyid; Siti Asriah Immawati; Srie Nuning Mulatsih (LPPM Politeknik Pratama, 2024)
An abstranct The lack of knowledge about investing with crypto makes many investors experience losses for investors, therefore this study aims to determine the effect of transaction security, ease of transactions and risk perception on crypto investment decisions among young people in Tangerang City. By using a sample of 200 people, collecting data through a questionnaire of 28 statements and using a 7-alternative answer liekrt scale and data analysis techniques using Smart PLS 4.0. The results of data analysis show that there is an influence between transaction convenience and risk perception on crypto investment decisions, while transaction security has no effect on investment decisions. Investors can assume that the platform or cryptographic technology used is safe and reliable, so transaction security is no longer a major concern for investment decisions. The recommendation in this study is the need to improve and improve the infrastructure of cryptographic transactions, this includes simplifying the transaction process, increasing transaction speed, and providing features that make it easier for users to invest.